2018
DOI: 10.1038/s41467-018-04288-4
|View full text |Cite
|
Sign up to set email alerts
|

Frequent pauses in Escherichia coli flagella elongation revealed by single cell real-time fluorescence imaging

Abstract: The bacterial flagellum is a large extracellular protein organelle that extrudes from the cell surface. The flagellar filament is assembled from tens of thousands of flagellin subunits that are exported through the flagellar type III secretion system. Here, we measure the growth of Escherichia coli flagella in real time and find that, although the growth rate displays large variations at similar lengths, it decays on average as flagella lengthen. By tracking single flagella, we show that the large variations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…In 2018, Zhao et al revisited E. coli flagellar growth by using biarsenical dyes to label flagellin with tetracysteine tag for single-cell observation [ 81 ] and showed that the flagellar growth of E. coli has frequent pauses due to insufficient flagellins [ 82 ]. Although a high fluctuation of the filament growth rate was observed similarly to that observed by Tuner.…”
Section: Flagellar Filament Constructionmentioning
confidence: 99%
“…In 2018, Zhao et al revisited E. coli flagellar growth by using biarsenical dyes to label flagellin with tetracysteine tag for single-cell observation [ 81 ] and showed that the flagellar growth of E. coli has frequent pauses due to insufficient flagellins [ 82 ]. Although a high fluctuation of the filament growth rate was observed similarly to that observed by Tuner.…”
Section: Flagellar Filament Constructionmentioning
confidence: 99%
“…The first approach induces nano-objects to execute non-reciprocal movements through body shape alteration, in order to displace the fluid around the body [158]. This is, for example, what happens in nature in micro-organisms provided with appendices [159,160] with Escherichia Coli bacteria being probably one of the must studied system. Escherichia Coli possesses long flagella on one side of the body that perform a non-time-reversible motion in order to move in a specific direction [161].…”
Section: Self-propelling Active Npsmentioning
confidence: 99%
“…Using cutting-edge biophysical methods, the torque-speed relationship [21-25], stepping [26], and switching [27, 28] of the BFM have been investigated. Very recently, the dynamic assembly of flagellar filaments has been characterized in real time [29-31]. However, questions still remain about whether flagella are permanent structures of the cell and, if not, the timing of their production and loss during different phases of the bacterial life cycle remain poorly understood.…”
Section: Main Textmentioning
confidence: 99%